An approach to the role of sex in the philosophy of Jean-Luc Nancy - Sánchez Mayor, Paula (Revista de Filosofía, 2024)
This paper aims to point out the place of sex in Jean-Luc Nancy’s philosophy. In his work, sex appears recurrently as the centre of gravity around which the impossibility of appropriation and closure orbits. When Nancy expounds his ontological-relational thinking about the relation of one to another and the relation of each one to his or her body, sex stands as the point of suture that precisely renders this relation unsaturable, opening it up again and again, thus revealing its plural and fractured character and destabilising the binary and dichotomous thinking that encloses the interminable recourse to unity. To this end, the question of the strangeness of the body and its difficulty in considering the ownership of something like my own body will be explored; on the other hand, the sexual relation as a paradigm of the relation without relation. In both aspects we find touching as a gesture that inaugurates the relation and whose structure prevents an appropriation of the touched object.